The existence of the National Police in Law Enforcement of Election Crimes Welcoming the Indonesian Democratic Party 2019 (Law Research Review Quarterly, 2018)
In the implementation of electoral processes and mechanisms often cause violations and crimes by supporters, cadres, and even directly to candidates for democratic party contestant. the police is a state institution whose duty is to deal with various violations as a form of law enforcement in all criminal and criminal acts, including violations of the organization of upcoming democratic parties. For this reason, this paper will discuss how the efforts and actions of the police are needed in creating quality and guaranteed general elections to get the title that the 2019 democratic party must be truly LUBER and JURDIL. Scientific writing is based on data and studies of normative law that focuses on positive legal norms and methods in drawing conclusions from matters that are general to specific matters. A democratic party is a general election carried out by the government for the people to elect heads of state and legislative members who will channel the aspirations of the people. Whereas the National Police is a state institution that has been regulated by laws and regulations in handling criminal offenses for elections for a democratic party that will soon be implemented. The police collaborate with the Prosecutor's Office, KPU, BAWASLU in analyzing, filtering and determining criminal offenses or violations of the administration of elections. T